Low modularity and specialization in a commensalistic epiphyte-phorophyte network in a tropical cloud forest - Francisco, Talitha M.; Couto, Dayvid R.; Garbin, Mario L.; Muylaert, Renata L. [UNESP]; Ruiz-Miranda, Carlos R. (Wiley-Blackwell, 2019)
Species interactions can shape the structure of natural communities. Such sets of interactions have been described as complex ecological networks, an example of which is the commensal network formed by epiphyte-phorophyte interactions. Vascular epiphytes germinate and grow on phorophytes (support trees), assuming a horizontal distribution (among the phorophyte species) and a vertical distribution (from the base of the tree trunk to the crown of phorophytes, i.e., through ecological zones). Here, we investigated the organization of these structural dimensions of the epiphyte-phorophyte network in a Brazilian tropical montane cloud forest. The analyzed network, comprising 66 epiphyte species and 22 phorophyte species, exhibited a nested structure with a low degree of specialization, a typical pattern for epiphyte-phorophyte networks in forests. The network was slightly modular, with 65% of the species common to three modules, and had vertical structure corresponding to the vertical organization of the phorophytes. The size (diameter at breast height) of phorophyte individuals influenced the network structure, possibly due to the increase in habitat area, the time available for colonization by epiphytes, and a greater number of microenvironments. We found that the distribution of the epiphyte species differed between the phorophyte ecological zones, with greater richness in the lower portions and greater abundance in the upper portions of the phorophytes. The results provide relevant guidance for future research on the characteristics and the vertical and horizontal organization of vascular epiphyte and phorophyte networks. in Portuguese is available with online material.
Keywords: Atlantic forest; facilitation; nestedness; plant-plant interaction; vertical stratification